Sexual Health of Trans Men Who Are Gay, Bisexual, or Who Have Sex with Men: Results from Ontario, Canada - Bauer, Greta R. (Taylor & Francis, 2013)
Recent reports have addressed the sexual health of female-to-male transgender or transsexual people who are gay, bisexual, and/or have sex with men (trans GB-MSM) using urban convenience samples. The Trans PULSE Project conducted a multimode, respondent-driven sampling survey in Ontario, Canada, in 2009–2010. Weighted estimates were calculated for trans GB-MSM (n = 173) for sexual orientation, behavior, partners, and HIV-related risk, as well as for psychosocial stressors and sexual satisfaction. An estimated 63.3% (95% CI [50.4, 73.5]) of trans men were GB-MSM (173/227). Results indicate great diversity in sexual behavior and experiences. Implications for sexual health promotion, counseling, and medical care are addressed.